Express Food Enterprise / Mohd Salehan Selamat... [et al.] - Selamat, Mohd Salehan; Albert, Evainesta; Dungkung, Merelene; Abdul Die, Nur Atiqah; Mohd Abidin, Ayu Andira (2012)
We are graduate student from University Technology Mara (UiTM), Kota Kinabalu, Sabah. Our company consists of five managers which are General Manager, Administrative Manager, Financial Manager, Marketing Manager and Operational Manager. We plan to sell the express food and drinks such as sausages, nuggets, dumpling, meatball, fishcakes, yong taufu, “kuih-muih” and etc. While, our drinks is made from juice fruits and sky juice. Our business premise will be located in UiTM, Kota Kinabalu, Sabah. We choose this business because we would like to fulfill one of human needs which are food and this kind of business has not yet performs in UiTM. We have planned to start our business in October 2013. Moreover, we borrowed money around RM64000.00. The product that we intend to sell is fast food and drinks because nowadays people want to get the fast service because the student routine life is so busy. This kind of food we serve are easy to prepare that’s why we have choose this service. While, the drinks are in lower cost and also easy to prepare and many people are interested to buy this drinks. We intend to sell it by using a mobile which is van mobile where this mobile will move throughout the UiTM area. The prospect of our business in term of revenue, we forecast that in early four monthly incomes, we expect that we does not have any income or we might get loss because we are new ventures and need to pay certain things such as van mobile rental and etc. We are intending to get the money to start the business by making loan with CIMB Bank at Kota Kinabalu, Sabah. In conclusion, we confidently sure that our business will be improve day by day and we will also expanding our business to another place such as Taman Indah Permai, Taman Seri Maju, Taman Kuala Menggatal and any places nearby with the success that we have achieve. Our business partnership also will contribute 51.4% to our business to ensure the loan is low that we will pay to the CIMB Bank.